RELIGIOUS PLURALITY AND INTERFAITH COEXISTENCE IN SABAH: REALITIES AND CHALLENGES FROM AN ISLAMIC PERSPECTIVE - Abu Bakar , Nor Iman Nabila; Ismail , Syaimak; Sabri , Siti Hanisah; Nayan, Nor Fatin Syuhaidah; Arom, Nurul Hidayah; Wan Halim, Wan Mohd Amjad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Religious tolerance plays a crucial role in maintaining social harmony within multicultural societies, particularly in regions with diverse ethnic and religious compositions such as Sabah, where Islam, Christianity, Buddhism, Hinduism, and indigenous belief systems coexist. This study explores the lived realities and emerging challenges of religious tolerance in Sabah, drawing from a qualitative content analysis of theological, legal, and socio-cultural sources. Findings reveal that the state's long-standing culture of openness, shaped by pre-colonial intercommunal interactions, interfaith marriages, and shared community spaces, has fostered a spirit of mutual respect and peaceful coexistence. Everyday practices, such as shared worship infrastructure and community collaboration during religious events reflect deep-rooted intercultural integration, reinforced by local wisdom and Islamic ethical values. While a general sense of religious harmony prevails, this study highlights those challenges to religious plurality in the lens of Islamic perspectives. The study identifies realities and challenges, including identity issues surrounding interfaith marriage, limited religious literacy among certain Muslim populations, and the risk of syncretic practices arising from uncritical adoption of local customs such as adat sogit. These realities highlight the fragile balance between cultural openness and religious integrity. While the spirit of tolerance remains strong, the lack of theological engagement within interfaith dialogues raises questions about the depth of religious plurality in Sabah. The study also finds that contextualof Islamic jurisprudence such as Fiqh Taayush, especially those rooted in Quran and Prophetic tradition offer a flexible yet firm framework for coexistence. This study therefore propose inclusive recommendations include strengthening Islamic education, enhancing public awareness of religious duties, and fostering institutional collaboration across. These steps are vital to preserving religious identity while sustaining interfaith harmony. Ultimately, the study contributes to the discourse on plurality by presenting Sabah as a dynamic case of how Islamic theological and legal perspectives can coexist with and support multicultural realities.